Refining the theory of basic individual values.[article]. - Schwartz, Shalom H.
We propose a refined theory of basic individual values intended to provide greater heuristic and explanatory power than the original theory of 10 values. The refined theory more accurately expresses the central assumption of the original theory that research has largely ignored: Values form a circular motivational continuum. The theory defines and orders 19 values on the continuum based on their compatible and conflicting motivations, expression of self-protection versus growth, and personal versus social focus. We assess the theory with a new instrument in 15 samples from 10 countries. Confirmatory factor and multidimensional scaling analyses largely support the predicted motivational order of the values. Analyses of predictive validity demonstrate that the refined values theory provides greater and more precise insight into the value underpinning of beliefs. Each value correlates uniquely with external variables. - (from the authors).
Keywords: Value theory; Value continuum; Basic values; Values structure; Motivation